Ultra-Low Anti-Müllerian Hormone Levels in Recurrent Cystic Ovarian Neoplasm: A Case Report - Merci Monica br Pasaribu; Naufal Arkan Abiyyu Ibrahim; Dayu Satriani (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2024)
Fertility has been a major issue in the management of cystic ovarian neoplasm. This case report presents an extreme case of ultra-low AMH levels in a young female with recurrent cystic ovarian neoplasm and analyzes the potential causes. A twenty-two-year-old female presented with stomach discomfort. The patient had undergone two surgeries for ovarian neoplasm within the last six years. The patient had another abdominal lump suspected to be a residual tumor mass. After further examination, the patient was diagnosed with cystic ovarian neoplasm. The laboratory findings showed low T4 levels, increased TSH levels, and ultra-low AMH levels (0.023 ng/mL). Management of cystic ovarian neoplasm should concern the effect on fertility. The AMH level can be used for pre-treatment counseling in these patients.